Optimizing the logistical routing of agricultural side-streams to a biogas plant for a circular bioeconomy implementation - Eloranta, Kasper; Koskela, Olli; Tampio, Elina; Kanniainen, Juho; Saari, Ulla A. (Elsevier BV, 2025)
The study addresses a Vehicle Routing Problem (VRP) that incorporates elements of the Biomass Collection Problem (BCP), using geo-spatial biomass data to determine pickup site locations and their content levels. Optimization techniques are proposed for the Biomass Routing and Biogas Production Problem (BRBPP). Biomass potential data was sourced from a national open data service used in Finland. The developed methodology includes models used to simulate and optimize components within a circular supply chain for transporting biomasses to biogas plants for renewable energy production. The study executes spatial information mapping for biomasses near the biogas plant and proposes an optimized routing plan for the optimization problem, aiming to execute a cost-effective logistic routing for continuous biogas production. The main contributions of the study are the tool and methodology developed for geospatial mapping of extensive datasets alongside modeling and optimizing logistic routing for biomass collection and transportation to centralized biogas plants.
Keywords: circular bioeconomy; logictic routing; optimization; biogas; simulation; genetic algorithms